Correlation of local and systemic expression of survivin with histopathological parameters of cutaneous melanoma - Jović, Milena; Cerović, Snežana; Zolotarevska, Lidija; Gačević, Milomir; Stanojević, Ivan; Miller, Karolina; Djukić, Mirjana; Saso, Luciano; Jauković, Ljiljana; Vojvodić, Danilo (Vojnosanitetski pregled, 2017)
Background/Aim. Survivin is a multifunctional protein abundantly expressed in tumors of various types, including melanoma. There are still sparse data regarding relationship of melanoma cell survivin expression with accepted histopathological characteristics as well as serum concentration.   The aim of this study was to investigate the association of local tumor survivin expression (primary tumor and metastatic lesions) and serum concentration with clinical and histopathological parameters in melanoma patients. Methods. The level of survivin expression was determined immunocytochemically in tumor tissue and with ELISA test in the serum of 84 melanoma patients diagnosed from 2009 to 2013 at the Institute for Pathology and Forensic Medicine and Institute for Medical Research at Military Medical Academy, Belgrade, Serbia. Results. The intensity of survivin expression was significantly higher in the patients whose tumor had ulceration, higher mitotic index, higher Clark and Breslow stage, that made vascular invasion or spread through lymphatic vessels in primary tumor, and was significantly higher in the patients with metastatic disease. Survivin expression and the number of survivin positive cells in metastatic lesions were significantly associated with the duration of disease free interval (DFI). The patients with high expression score had almost double shorter DFI comparing to those with weak local survivin expression and a small number of survivin+ cells (9 ± 7 vs 19 ± 13 months, respectively). The degree of tumor infiltrating lymphocytes presence in tumor tissue was significantly associated with serum survivin concentration, with lowest average level detected in samples of patients with the highest degree of infiltration. Serum survivin concentrations were highest in samples of melanoma patients with IA American Joint Commission on Cancer (AJCC) clinical stage, pT1a histological stage, patients whose tumors were still in horizontal growth phase, without signs of lympho-hematological disease spreading, with the highest number of mitoses and the smallest Clark index. Conclusion. Survivin expression in tumor tissue and its serum concetration significantly correlate with clinical and histopathological parameters. Serum levels could be important in initial follow-up as indicators of  those patients that would have aggressive local tumor growth and spreading. Survivin determination in tumor tissue is of great significance in estimation of DFI.
Keywords: neoplasm proteins; biological markers; melanoma; histology; immunohistochemistry; sensitivity and specificity